Tiesiskās aizsardzības process - Balcere, Līga (Latvijas Universitāte, 2012)
Bakalaura darba mērķis ir aplūkot vienu no Maksātnespējas likumā paredzētajām procedūrām – tiesiskās aizsardzības procesu. Šīs metodes izmantošana ir līdzeklis, kā izvairīties no maksātnespējas, tās efektīva piemērošana ar mērķi pasargāt uzņēmumu no maksātnespējas ir nozīmīgs tiesisks līdzeklis šā brīža ekonomiskās situācijas apstākļos. Bakalaura darbā pētītas tiesiskās aizsardzības procesa piemērošanas aktuālākās problēmas un izstrādāti priekšlikumi nepieciešamajām izmaiņām Maksātnespējas likumā. Darbā izmantota salīdzinošā metode, salīdzinot šo tiesību institūtu ar citu valstu līdzīgiem tiesību institūtiem.

The goal of bachelors’ thesis is to look at one of the insolvency proceedings – legal protection process. Creditors have always been seeking to recover debts and debtors have always sought to get rid of their indebtedness. These two divergent positions of debt recovery and the release of the debts form the basis for the regulation of insolvency. Legal protection process serves as a means of avoiding insolvency. Thus, effective application of legal protection process is an important legal tool with the purpose to protect companies from insolvency. The comparative method is applied in this thesis. Latvian regulatory framework is compared to the methods for insolvency issues used in other countries to discuss changes in Latvia’s applicable laws and regulations. Necessity of amendments to the Insolvency Law is evidenced by ongoing intensive public discussion.
Legal Protection Process
Keywords: Juridiskā zinātne